Left atrial compliance: an overlooked predictor of clinical outcome in patients with mitral stenosis or atrial fibrillation undergoing invasive management - Hrabia, Joanna B.; Pogue, Elahn P.L.; Zayachkowski, Alexander G.; Długosz, Dorota; Kruszelnicka, Olga; Surdacki, Andrzej; Chyrchel, Bernadeta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2018)
In the assessment of cardiovascular disease, the clinical significance of left atrial (LA) pressure-volume relations has largely been overlooked in contrast to left ventricular (LV) compliance. However, LA compliance has recently gained more attention. Net atrioventricular compliance (Cn), a joint measure of LA and LV compliance, can be calculated non-invasively by a previously validated method using parameters from standard echocardiography. Compliance measurement may be of relevance in selected clinical settings. First, subjects with low Cn are more likely to have their mitral valve area overestimated by the traditional mitral pressure half-time method. Consequently, low Cn in mitral stenosis, usually resulting from reduced LA compliance, can be mistaken for mild mitral stenosis. Second, low Cn independently predicted pulmonary hypertension and disease progression in medically treated mitral stenosis, and late cardiovascular complications after successful percutaneous mitral valvuloplasty. Decreased LA compliance also accounts for stiff LA syndrome, a rare complication of radiofrequency catheter ablation for atrial fibrillation, manifesting as otherwise unexplained heart failure with elevated LA pressure and pulmonary hypertension. Finally, depressed pre-ablation LA stiffness index, i.e. the ratio of the change in LA pressure to the corresponding change in LA volume during passive LA filling, was an independent predictor of arrhythmia recurrence. Thus, LA stiffening translates into adverse clinical outcomes in patients with mitral stenosis or atrial fibrillation undergoing interventional procedures. Whether reduced LA compliance after LA appendage occlusion can result in the LA stiff syndrome, has not been reported so far.